1991
DOI: 10.1111/j.1349-7006.1991.tb01753.x
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Heterogeneous Distribution of Tumor Blood Flow in the Rat

Abstract: Angioarchitectures of ascites hepatoma AH109A and Sato lung carcinoma (SLC) were quantitatively compared by measuring the following morphometric parameters: vascular density, vascular length, distance hetween tissues and their nearest blood vessel, and total length of microvascular network per unit area. When the vascular networks in these two types of tumors were compared in the initial stage, the morphological parameters were almost identical. Correlations between tumor size and the number of starting vessel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
15
0

Year Published

1992
1992
2011
2011

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 29 publications
(17 citation statements)
references
References 19 publications
2
15
0
Order By: Relevance
“…1,2) This observation was consistent with our results described above. However, why did AC-7700 exhibit antitumor activity in the advanced tumor model despite poor drug delivery?…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…1,2) This observation was consistent with our results described above. However, why did AC-7700 exhibit antitumor activity in the advanced tumor model despite poor drug delivery?…”
Section: Discussionsupporting
confidence: 93%
“…It has been reported that, as tumors grow, low-or no-flow areas are generated in malignant tissue and interstitial fluid pressure also increases. [1][2][3] Clinical tumors at advanced stage often grow slowly, and their tumor cell population in the growth phase decreases compared with that in subcutaneous (s.c.) rodent tumors. These factors markedly reduce drug accessibility to malignant tissue and tumor cell sensitivity to chemotherapeutic agents whose effectiveness depends on the cell cycle.…”
mentioning
confidence: 99%
“…Tumour blood flow, tissue oxygenation, and energetic status may vary over a wide range in different tumour entities and may show pronounced heterogeneities within one tumour (Jain, 1988;Vaupel et al, 1989b;Hori et al, 1991). These intratumoural variabilities make it difficult to establish correlations between these parameters, if data were averaged over the entire tumour.…”
mentioning
confidence: 99%
“…Also unlike normal tissues, tumour tissues have similar arterial pressure and a lower venous pressure (Peters et al 1980). Most blood vessels in the internal regions of a tumour are veins or venules, whereas the peripheral regions of a tumour have few arteries or arterioles (Hori et al 1990(Hori et al , 1991. Therefore, the arteriole-venule pressure difference as a driving force for blood flow is negligible in the central region of a tumour, but is greater in the periphery.…”
Section: Tumour Blood Flowmentioning
confidence: 99%